Fibrous materials as technological additives in the production of butadiene-styrene rubbers and elastoplastics - Nikulin, Sergey; Pugacheva, Inna; Misin, Viacheslav; Sedyh, Valeriy (Publishing House of Lviv Polytechnic National University, 2008)
Prospects of recycling of waste products of fibrous materials (cotton, viscose, kapron) for obtaining of elastic composite materials are shown by creation of fibre-latex composition with subsequent coagulation and vulcanization of the filled rubber. The optimum contents of the fibre and its length is determined. Показано перспективність утилізації відходів волокнистих матеріалів (бавовняного, віскозного і капронового) для одержання еластичних композиційних матеріалів внаслідок створення композиції волокно–латекс з наступною коагуляцією і вулканізацією наповненої суміші. Визначено оптимальний вміст волокна і його довжину.
Волокнисті матеріали - як технологічні додатки у виробництві бутадієн-стирольного каучуку і гум
Keywords: composition; rubber; fibre; latex; vulcanizate; композиція; каучук; латекс; волокно; вулканізат